PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MURID PADA MATERI KELISTRIKAN - Safiqoh Arbaatin, Nur; Martini, Martini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking skills have an important role in 21st century development. In fact, there are still students who cannot complete problems with critical thinking indicators. This study aims to improve the critical thinking skills of students in class IX B of SMP Labschool UNESA 1 by applying a guided inquiry learning model. This study uses a quantitative method with a pre-experimental design and a one-group Pre-test-Post-test design. The research subjects were 32 students in class IX B of SMP Labschool UNESA 1. The data collection technique used tests. The application of the guided inquiry learning model for electrical material proved to be able to improve students' critical thinking skills with a post-test completion rate of 64% in the good category, with an average N-Gain score of 0.5 in the moderate category. In conclusion, the guided inquiry learning model can improve students' critical thinking skills in electrical material.